Becoming intercultural an integrative theory of communication and cross-cultural adaptation - Kim, Young Yun.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2001)
This book looks at the movements of immigrants and refugees and the challenges they face as they cross cultural boundaries and strive to build a new life in an unfamiliar place. It focuses on the psychological dynamic underpinning their adaptation process; how their internal conditions change over time; the role of their ethnic and personal backgrounds and of the conditions of the host environment affecting the process.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intercultural communication; Assimilation (Sociology); Emigration and immigration -- Psychological aspects; Electronic books